2001
DOI: 10.1037/0096-1523.27.2.411
|View full text |Cite
|
Sign up to set email alerts
|

Variability in isochronous tapping: Higher order dependencies as a function of intertap interval.

Abstract: Isochronous serial interval production (ISIP) data, as from unpaced finger tapping, exhibit higher order dependencies (drift). This fact has largely been ignored by the timing literature, one reason probably being that influential timing models assume random variability. Men and women, 22-36 years old, performed a synchronization-continuation task with intertap intervals (ITI) from 0.4 s to 2.2 s. ISIP variability was partitioned into components attributable to drift and 1st-order serial correlation, and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
136
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(150 citation statements)
references
References 41 publications
14
136
0
Order By: Relevance
“…The higher duration difference thresholds of SDI at intervals around 1000 ms, in contrast, would be interpreted as based on disturbances of additional cognitive processes that come into play only at longer intervals. Based on prior studies using tapping tasks, there is evidence that a specific temporal processing function occurs in a time range between approximately 300 ms and one or two seconds (Madison, 2001;Mates et al, 1994;Wittmann et al, 2001). In fact, inferring from a recent synchronization tapping study employing a secondary attention task, Miyake et al (2004) concluded that in a time range between 450 to 1500 ms automatic processing that is not strongly affected by attention, whereas attention and working memory affect intervals in the range between 1800 and 3600 ms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher duration difference thresholds of SDI at intervals around 1000 ms, in contrast, would be interpreted as based on disturbances of additional cognitive processes that come into play only at longer intervals. Based on prior studies using tapping tasks, there is evidence that a specific temporal processing function occurs in a time range between approximately 300 ms and one or two seconds (Madison, 2001;Mates et al, 1994;Wittmann et al, 2001). In fact, inferring from a recent synchronization tapping study employing a secondary attention task, Miyake et al (2004) concluded that in a time range between 450 to 1500 ms automatic processing that is not strongly affected by attention, whereas attention and working memory affect intervals in the range between 1800 and 3600 ms.…”
Section: Discussionmentioning
confidence: 99%
“…Different temporal processing mechanisms seem to be involved for different time scales (Buhusi and Meck, 2005;Mauk and Buonomano, 2004;Wittmann, 1999). Temporal integration windows of around 250 to 500 ms (Rammsayer, 1999;Wittmann et al, 2001), of around 1 second (Madison, 2001) and for intervals up to 2 to 3 seconds (Fraisse, 1984;Pöppel, 1997;Wittmann et al, 2007) have been postulated. To probe temporal processing at a variety of time scales, from the milliseconds range to the seconds range, a set of tasks was employed assessing duration discrimination, temporal reproduction, time estimation, and paced finger tapping.…”
Section: Introductionmentioning
confidence: 99%
“…We have investigated this issue using a simple motor timing behavior, isochronous serial interval production (ISIP), where the participants produce self-paced tapping movements with an even beat. The temporal variability of the produced intervals can be divided into local tap-to-tap variability (Local) and slow drift in tapping frequency (Drift) (Madison 2001;). We have earlier argued that Drift depends on short-term memory of previously performed intervals, and is likely to be more sensitive to top-down influences than Local, which appears to reflects unsystematic random noise (Madison 2001;Madison and Delignières 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the detrending procedure applied here would have been insufficient to compensate for the ensuing nonlinearities in the produced drift. Madison (2001) showed that this kind of influence results in lag-one autocorrelation estimates closer to zero (i.e., less negative than the WKmodel predicts). Despite the deviations from linearity and the fact that drift can be modeled in a variety of ways (Madison 2001;Collier and Ogden 2004), the linear fit found here was well within the range of the constant frequency conditions, implying that the subjects followed the instructions to a satisfactory degree.…”
Section: Discussionmentioning
confidence: 97%
“…The most likely explanation of this finding is that subjects did not perform a purely linear drift. There is evidence that drift perception is governed by a detection threshold for a change in tempo (e.g., Madison 2001). If drift production involves a similar process, drift would show abrupt changes and would not be linear and monotonic.…”
Section: Discussionmentioning
confidence: 99%